Designing Instructional Material to Promote Intercultural Competence: A Preliminary Study - Dian Indah Silfia; Ekaning Dewanti Laksmi; Niamika El Khoiri (The Journal of English Literacy Education: The Teaching and Learning of English as A Foreign Language, 2023)
One of Sekolah Penggerak’s pilot schools proposed an English Extracurricular program to develop students' intercultural competence as specified in the Pancasila Student Profile (PSP). Scholars believe that instructional material is among the most significant sources for teaching cultural, social, and moral values to students and for providing language input. Nevertheless, the demands of students have not been fully addressed to develop instructional material. This study examined the program’s potential to help students develop their intercultural competence, the challenges encountered by teachers, the needs of students in achieving the program goals, and the instructional material required to meet those needs. A qualitative descriptive design was employed to gather the information from the school principal and a classroom teacher mandated to manage the program. The data was collected through a focus group interview using open-ended questions and analyzed based on the program’s purposes, challenges, and instructional materials needed. The finding portrayed that students’ intercultural competence can be achieved if the teacher and students have relevant learning guidance regarding the goals. However, the book does not suit the student's needs and the program's goals, so the teacher encounters challenges in providing reliable materials. In addition, the instructional material needs to include the concept of the natural language acquisition process and differentiation-based instruction to ensure that all students are well accommodated in achieving the program goals. Further studies with related interests are recommended to develop such instructional material based on the data presented and further explore the student’s needs in the wider context.